Non‐invasive prenatal testing for trisomy 21 based on analysis of cell‐free fetal DNA circulating in the maternal plasma. (May 2015) - Alberti, A.; Salomon, L. J.; Le Lorc'h, M.; Couloux, A.; Bussières, L.; Goupil, S.; Malan, V.; Pelletier, E.; Hyon, C.; Vialard, F.; Rozenberg, P.; Bouhanna, P.; et al.
Abstract Objective By‐the‐book implementation of non‐invasive prenatal test and clinical validation for trisomy 21. Study Design Publicly funded prospective study of 225 cases. Women at risk for trisomy 21 > 1/250 based on combined ultrasound and serum markers during first or second trimester were eligible following an informed consent. The technique was established from the available literature and performed on 10 mL of venous blood collected prior to chorionic villus sampling or amniocentesis. Investigators were blinded to the fetal karyotype. Results were expressed in Z‐scores of the percentage of each chromosome. Results Among 976 eligible cases, 225 were processed: 8 were used for pretesting phase and 23 to build a reference set. One hundred thirty six euploid cases and 47 with trisomy 21 were then run randomly. Eleven cases yielded no result (4.8%). Z‐scores were above 3 (7.58+/−2.41) for chromosome 21 in all 47 trisomies and in none of the euploid cases (0.11+/−1.0). Z‐scores were within normal range for the other chromosomes in both groups. Using a cut‐off of 3, sensitivity and specificity were of 100% 95% CI [94.1, 100] and 100% 95% CI [98, 100], respectively. Conclusion Non‐invasive prenatal test for trisomy 21 is a robust strategy that can be translated from seminal publications. Publicly funded studies should refine its indications and cost‐effectiveness in prenatal screening and diagnosis. © 2015 John Wiley & Sons, Ltd.